Implementing Student Life Regulations for Religious Character Development in Islamic Schools - Hafizah; Chusniatun (Fakultas Agama Islam Universitas Billfath, 2025)
This research aims to describe the implementation of religious character building at CT Arsa Foundation Sukoharjo High School by integrating faith values in every aspect of education. In facing the challenges of globalization and an increasingly complex moral crisis, CT Arsa Foundation High School plays a crucial role in shaping a young generation that is not only intellectually intelligent but also has a strong religious character. The method used in this research is descriptive qualitative. The research subjects consisted of homeroom teachers who also acted as foster guardians, Islamic Religious Education teachers, and three students who the Islamic Religious Education teacher directly selected. Data collection techniques used interviews, observation, and document analysis. Thematic Analysis was used in the research analysis. The results show that religious character building is successfully implemented through a holistic approach that includes various scheduled activities, such as congregational prayer, morning roll call, evening roll call, and tadarus, which aim to internalize the values of faith in daily life. In addition, implementing the Learner Life Regulations (PERDUPDIK) also plays an important role in strengthening this religious character-building process. Thus, SMA Unggulan CT Arsa Foundation not only produces a generation with religious character and is ready to face global challenges, but also a generation that has a good character.